METHODS OF STUDYING THE VARIOUS CAUSES AND EFFECTS OF STRESS IN TEACHERS (ResearchJet Journal of Analysis and Inventions, 2021)
The article presents the problem of stress tolerance in the professional activity of a teacher is considered. It is noted that the stress resistance of students in educational activities is a complex property of the individual, which is characterized by the necessary adaptation of the student to the influence of external and internal factors in the course of educational activities. The factors influencing the development of stress tolerance and a positive attitude to learning activities are considered.